2019
DOI: 10.1523/jneurosci.0975-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Failure of Spike Propagation in Primary Afferent Neurons during Tactile Stimulation

Abstract: Primary afferent neurons convey somatosensory information to the CNS. Low-threshold mechanoreceptors are classified as slowadapting (SA) or rapid-adapting (RA) based on whether or not they spike repetitively during sustained tactile stimulation; the former are subclassified as Type 1 or 2 based on the regularity of their spiking. Recording in vivo from DRGs of mice, we observed irregular-and regular-spiking units consistent with SA1 and SA2 low-threshold mechanoreceptors, but some units, which we labeled "semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 75 publications
(98 reference statements)
6
20
0
Order By: Relevance
“…Single-unit recordings (Fig. 5) revealed that evoked spikes in C and A fibers do fail occasionally under basal conditions (at a rate of ~16% in C and ~6% in A fibers), which was consistent with a recent report (18). Thus, basal filtering does exist but when measuring evoked single-unit spikes it is much lower than ~50% mismatch seen in our multi-unit SN/DR recordings.…”
Section: Discussionsupporting
confidence: 92%
“…Single-unit recordings (Fig. 5) revealed that evoked spikes in C and A fibers do fail occasionally under basal conditions (at a rate of ~16% in C and ~6% in A fibers), which was consistent with a recent report (18). Thus, basal filtering does exist but when measuring evoked single-unit spikes it is much lower than ~50% mismatch seen in our multi-unit SN/DR recordings.…”
Section: Discussionsupporting
confidence: 92%
“…Of course, the frequency threshold and the number of spikes required to cause spike failure will depend on the specifics of the expression of neuronal conductances, and will likely show variability as a consequence of variable channel densities (46). Additionally, intrinsic channel noise can cause spike failure (4,27), and the normal function of the Na/K ATPases requires ATP, the supply of which has a limit (35). Both a shortage of ATP after continuous firing and channel noise can further reduce axonal reliability of propagating spikes.…”
Section: Discussionmentioning
confidence: 99%
“…1B). However, neurons can fire at high frequencies when animals receive stimuli or undergo behavior changes (7,(25)(26)(27). With continuous high frequency spiking, [Na + ] can accumulate if subsequent spikes occur before the complete recovery of a preceding spike elicited [Na + ] rise.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…8). But one must also consider that energy efficiency trades off with functional considerations like propagation safety factor 61 . Target values might emerge from this competition 62 but such mechanisms were beyond the scope of the current study.…”
Section: Most Of the Ion Channel Combinations Producing A Consistent mentioning
confidence: 99%